Estudo da influência do tempo de reação e do teor de “Na” na síntese de zeólitas - RODRIGUES, Emerson Cardoso (Universidade Federal do Pará, 2013)
This work aims to synthesize zeolite type "A" using as raw kaolin filler. The synthesis of zeolites was performed in a short time and without agitation. The starting materials and the product were identified and characterized by X ray Diffraction (XRD), Fluorescence Spectrometry, X Ray, Scanning Electron Microscopy (SEM), Grain Size Analysis and Gravimetric and Differential Thermal Analysis (DTA and TG). In the synthesis process was used as the silica source and the alumina metakaolinite, which has been calcined at a temperature of 600 ° C for 2 hours threshold firing in a muffle type furnace. As a source of sodium was used a solution of sodium hydroxide 5 M in the system was also added distilled water. Various syntheses were performed inside an oven at 110 °C. The variation in reaction time and sodium content were the variables in the process. The results of the synthesis of zeolite A proved satisfactory, especially in time of 10 h with a ratio Al / Na = 0.57. The reaction time and amount of sodium are directly proportional to the formation of another phase called zeolitic Hydroxysodalite. From the zeolite A, by ion exchange with a solution of calcium chloride was obtained zeolite 5A without agitation.